Resident Perceptions and Parcel-Level Performance Outcomes of Mangroves, Beaches, and Hardened Shorelines After Hurricane Irma in the Lower Florida Keys - O’Donnell, Kiera L.; Tomiczek, Tori; Scyphers, Steven B. (Frontiers in Environmental Science, 2022)
Hurricanes have large and lasting effects along coastlines, representing one of the deadliest and costliest natural hazards. Among the rapidly growing literature on the impacts of hurricanes, an increasing topic of interest is the potential role of mangroves, and other coastal habitats, as nature-based strategies (NBS) for coastal defense. In addition to coastal protection, NBS have been shown to provide many ecological, economic, and social co-benefits. However, few studies have assessed coastal resident perceptions or residential-scale performance of NBS, particularly in the wake of major hurricanes. Through a survey of 288 residents of the Lower Florida Keys one year after Hurricane Irma, this paper describes hurricane impacts on mangroves, beaches, and hardened shorelines. Specifically, we measured perceptions of shoreline damage and shoreline effectiveness for coastal protection at the community- and parcel-levels. At the parcel scale, we also measured performance outcomes through the cost to repair or replace residential shorelines. At both community- and parcel-levels, beaches were perceived as the most damaged shoreline type, followed by mangroves, then hardened shorelines as the least damaged. However, the average cost to repair or replace parcel-level mangroves ($64.33 (USD) ±SE 58.08 per meter) was less than hardened shorelines ($105.14 (USD) ±SE 38.57 per meter). Additionally, many residents (44%) reported that no repair or recovery actions were needed after the storm for damaged mangroves, whereas many damaged hardened structures required at least minor repairs (29.5%). Mangroves were also perceived as the most effective shoreline for storm protection (54% very to extremely effective) at the community-level. Our findings indicate local community-level awareness of the storm protective properties mangroves provide but also display a disconnect between perceptions and performance outcomes at parcel scales. Although mangroves cost less to repair and are perceived as the most effective at storm protection, the majority of Florida Keys residents own hardened shorelines. Considering the diverse co-benefits mangroves provide and the local support mangroves have, their conservation and restoration could be well-supported for coastal adaptation.